(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Bell’s palsy is the common acute mono-neuropathy, and is commonly associated with facial paralysis or weakness of facial nerve. It is unilateral facial nerve paresis or paralysis. The cause of Bell’s palsy is suspected to be herpes simplex virus infection of nerve.The nerve get swollen because of this viral infection and is compressed in its canal as it passes through the temporal bone. Grading systems for the assessment of movements and asymmetry of face in Facial palsy are divided into computer-based and traditional grading systems. The program that uses Kinect Azure provides assessment method for evaluation of asymmetry of face at rest and the rating of facial palsy during voluntary activity of various areas over face. This study aims to investigate the intervention of facial palsy by video self modelling with the use of Kinect Azure. Methods: 20 participants will be selected. Each group will include 10 subjects. Group A will receive conventional treatment, electrical muscle stimulator(EMS) ,and visual feedback. Group B(Experimental group) will receive conventional treatment ,electrical muscle stimulator and video self modelling. Each participant would be presented with their own videotape of video self-modeling, which included the best attempts at their evenest acts (smiles).Following 2 weeks of tape viewing the actions will be assessed. The outcome of the treatment will be assessed by Kinect Azure. Discussion: Traditional methods for documentation of treatment effect have been through scales and questionnaires which at times are little complex and also difficult for patients to interpret. Hence this experimental and comparative study aims at focusing on the effective use of Kinect to document outcome for bell’s palsy